1999
DOI: 10.1289/ehp.99107649
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and mortality of workers at Oak Ridge National Laboratory: positive associations for doses received at older ages.

Abstract: We examined associations between low-level exposure to ionizing radiation and mortality among 14,095 workers hired at the Oak Ridge Nationl Laboratory between 1943 and 1972. Workers at the facility were individually monitored for external exosure to ionizing radiation and have been followed through 1990 to ascertain cause of death information. Positive associations were observed between low-level exposure to external ionizing radiation and mortality. These associations were larger for doses received after 45 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…There are suggestions in these data that the solid cancer ERR increases with increasing age at first exposure or attained age (age at death) and that the leukemia ERR increases with increasing age at first exposure. These patterns appear to contradict what one would expect on the basis of the atomic bomb survivors (20,24) and mechanistic considerations (25)(26)(27)(28), but some analyses of U.S. nuclear workers have suggested similar general patterns (29,30). To try to better understand these unexpected temporal patterns, we performed some more detailed descriptive analyses.…”
Section: Discussionmentioning
confidence: 80%
“…There are suggestions in these data that the solid cancer ERR increases with increasing age at first exposure or attained age (age at death) and that the leukemia ERR increases with increasing age at first exposure. These patterns appear to contradict what one would expect on the basis of the atomic bomb survivors (20,24) and mechanistic considerations (25)(26)(27)(28), but some analyses of U.S. nuclear workers have suggested similar general patterns (29,30). To try to better understand these unexpected temporal patterns, we performed some more detailed descriptive analyses.…”
Section: Discussionmentioning
confidence: 80%
“…Although some studies of nuclear workers have not reported results for this category of cancer mortality, results can be compared with those for all cancers except leukaemia, which are similar 4. Significant associations between dose and risk for all cancers except leukaemia were observed in several nuclear worker cohorts,4 8 13 27 28 noticeably in the 15-country study4 and the last UK National Registry of Radiation Workers (NRRW) analysis 8. The magnitude of the ERR/Sv estimated in our study appears similar to that estimated in the 15-country study after exclusion of the Canadian cohort 4.…”
Section: Discussionmentioning
confidence: 96%
“…In other workforces (Richardson and Wing 1999; Vrijheid et al 2007), there were generally no statistically significant trends of circulatory disease with dose (Table 1). It should be noted that these studies overlap, and in particular there is substantial inclusion of the study populations of the studies of Richardson and Wing (1999) and Muirhead et al (2009) within that of the IARC study (Vrijheid et al 2007).…”
Section: Methodsmentioning
confidence: 94%